Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.4028/www.scientific.net/amr.787.771
|View full text |Cite
|
Sign up to set email alerts
|

Seismic Tests on RC Building Exterior Joints with Wide Beams

Abstract: Reliable assessment procedures of existing RC buildings are currently available, and have been introduced in the Italian and European codes reporting new rules for seismic analysis. However, further studies are required in order to further improve such procedures and, specifically, obtain more accurate data on the behavior of beam-column joints, whose role on the global behavior of framed RC buildings can be crucial. Until now studies on this issue have been mainly devoted to joint specimens with stiff beams, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 5 publications
0
20
0
Order By: Relevance
“…The experimental program related to this study is reported in detail in [3]. However, for sake of clarity, a short summary is reported in the following.…”
Section: Experimental Campaignmentioning
confidence: 99%
See 2 more Smart Citations
“…The experimental program related to this study is reported in detail in [3]. However, for sake of clarity, a short summary is reported in the following.…”
Section: Experimental Campaignmentioning
confidence: 99%
“…The top column displacement was acquired by means of a wire transducer, while the deformations at the beam-column intersection were acquired through Linear Variable Displacement Transducers (LVDT). More details on the instrumentation and test apparatus can be found in [3]. …”
Section: Experimental Campaignmentioning
confidence: 99%
See 1 more Smart Citation
“…(6,7) DCH (q=3.5) ≈30dbi ≈48 (6,7) -0.25hc (9,11) 0.25hc 0.25hc (16) min{L/8;8hf;hb; hc·{0.5;0.75} (18) }; min{L/8;8hf;3hb} (19) 0.25hc (22) 90% (24) Spain: NCSE-02 (2002) [14] -33%) ≈36dbi ≈55 (6,7) min{0.5hb; 0.5bc (8) } (10) -0.5bc (14) 0.25hc (8) hf·{0;2;0;2} (17) - (21 Current version of EC8 does not cover flat slab, 1.5 is the basic assumption for elastic design; new version in progress (1) For DLS but obtained from ULS displacements (2) Specific for ULS (3) Obtained from specific DLS demand spectrum (4) Depending on ag and number of storeys (5) Sufficient stiffness to ensure frame -not cantilever-behaviour in all columns (6) Formulation depending in most of the cases on ductility class, material strengths, axial load, reinforcement ratios and location of the joint (7) Considering ϕw=16mm (8) Edge beams not explicitly considered (9) Not for low-ductility design (10) Referred to gross section, not to web (11) Referred to the 90% of the required flexural reinforcement; remaining 10% within (19) (12) Required transverse beam for external connections or internal connections with moment inversion (13) Not mandatory, only for taking advantage of the column compression on the bond behaviour (14) Higher values only if proper perpendicular reinforcement is placed (15) Further research is needed (16) Also reciprocal requirement for columns in the case of wide column -narrow beam connection (17) Exterior connection with and without transverse beam, and anal...…”
Section: Code Provisions On Wide-beam Framesmentioning
confidence: 99%
“…Literature evidence on WBF is mainly based on experimental and analytical studies focusing on local structural behaviour [ [19]. Still, there is a lack of systematic studies addressing global performances of WBF against equivalent DBF fulfilling the requirements of different codes.…”
Section: Nomenclaturementioning
confidence: 99%